The Warburg Effect Suppresses Oxidative Stress Induced Apoptosis in a Yeast Model for Cancer - Ruckenstuhl, Christoph; Büttner, Sabrina; Carmona-Gutierrez, Didac; Eisenberg, Tobias; Kroemer, Guido; Sigrist, Stephan J.; Fröhlich, Kai-Uwe; Madeo, Frank (PLOS ONE, 2009)
Background Otto Warburg observed that cancer cells are often characterized by intense glycolysis in the presence of oxygen and a concomitant decrease in mitochondrial respiration. Research has mainly focused on a possible connection between increased glycolysis and tumor development whereas decreased respiration has largely been left unattended. Therefore, a causal relation between decreased respiration and tumorigenesis has not been demonstrated. Methodology/Principal Findings For this purpose, colonies of Saccharomyces cerevisiae, which is suitable for manipulation of mitochondrial respiration and shows mitochondria-mediated cell death, were used as a model. Repression of respiration as well as ROS-scavenging via glutathione inhibited apoptosis and conferred a survival advantage during seeding and early development of this fast proliferating solid cell population. In contrast, enhancement of respiration triggered cell death. Conclusion/Significance Thus, the Warburg effect might directly contribute to the initiation of cancer formation - not only by enhanced glycolysis - but also via decreased respiration in the presence of oxygen, which suppresses apoptosis.